Analisis Kesalahan Dalam Menyelesaikan Soal Integral Taktentu Dengan Metode Newman Ditinjau Dari Kemampuan Matematis - Arena Iriani; Nyoman Sridana; Tabita Wahyu Triutami; Syahrul Azmi (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to describe errors in solving indefinite integral problems of algebraic functions based on Newman's procedure in terms of the category of mathematical ability. This type of research is descriptive with a qualitative approach. The research subject is class XII IPS 1 SMAN 5 Mataram in the academic year 2022/2023. The results showed (1) High-ability students made mistakes at the process skill stage due to the lack of giving practice questions using the partial method. (2) Students who are capable are making mistakes at the transformation stage due to incorrectly substituting the values ​​obtained at the example stage, and errors in the process skill stage because they cannot simplify terms containing the variable x. (3) Low-ability students make mistakes at the reading stage because they don't know the mention of the